FACTORS ASSOCIATED WITH QUALITY OF LIFE IN ELDERLY PATIENTS WITH KNEE OSTEOARTHRITIS (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the associations of SF-36, including the Physical Component Summary (PCS) and Mental Component Summary (MCS), with sociodemographic factors, pain severity by VAS, and WOMAC domains in elderly patients with knee osteoarthritis (KOA).Subjects and Methods: A cross-sectional study was conducted in 333 patients aged ≥60 years with KOA diagnosed according to the 1991 ACR criteria at the University Medical Center Ho Chi Minh City from December 2023 to May 2024. Quality of life was assessed using SF-36, pain severity using VAS, and functional limitation using WOMAC. Data were analyzed using t-tests, ANOVA, Pearson correlation, and multivariable linear regression.Results: SF-36 score decreased with increasing pain severity (p < 0.001); the mild pain group had the highest score (49.46 ± 14.31), and the severe pain group the lowest (28.94 ± 12.38). WOMAC 1 and WOMAC 3 were inversely correlated with PCS, MCS, and total SF-36 score, with WOMAC 3 showing the strongest correlation with total SF-36 score (r = −0.359; p < 0.001). In multivariable analysis, VAS and WOMAC 3 were associated with total SF-36 score, while age, sex, and education level were associated with some SF-36 components.Conclusion: PCS, MCS and total SF-36 score were associated with age, sex, education level, pain severity and functional limitation in elderly patients with KOA.
Keywords: knee osteoarthritis, elderly, SF-36, PCS, MCS, VAS, WOMAC.